Luminescence and Light‐Driven Energy and Electron Transfer from an Exceptionally Long‐Lived Excited State of a Non‐Innocent Chromium(III) Complex. Issue 50 (31st October 2019) - Treiling, Steffen; Wang, Cui; Förster, Christoph; Reichenauer, Florian; Kalmbach, Jens; Boden, Pit; Harris, Joe P.; Carrella, Luca M.; Rentschler, Eva; Resch‐Genger, Ute; Reber, Christian; Seitz, Michael; et al.
Abstract: Photoactive metal complexes employing Earth‐abundant metal ions are a key to sustainable photophysical and photochemical applications. We exploit the effects of an inversion center and ligand non‐innocence to tune the luminescence and photochemistry of the excited state of the [CrN6 ] chromophore [Cr(tpe)2 ] 3+ with close to octahedral symmetry (tpe=1, 1, 1‐tris(pyrid‐2‐yl)ethane). [Cr(tpe)2 ] 3+ exhibits the longest luminescence lifetime ( τ =4500 μs) reported up to date for a molecular polypyridyl chromium(III) complex together with a very high luminescence quantum yield of Φ =8.2 % at room temperature in fluid solution. Furthermore, the tpe ligands in [Cr(tpe)2 ] 3+ are redox non‐innocent, leading to reversible reductive chemistry. The excited state redox potential and lifetime of [Cr(tpe)2 ] 3+ surpass those of the classical photosensitizer [Ru(bpy)3 ] 2+ (bpy=2, 2′‐bipyridine) enabling energy transfer (to oxygen) and photoredox processes (with azulene and tri( n ‐butyl)amine). Abstract : Super‐long luminescence lifetime (4500 μs) at room temperature, high quantum yield (8.2 %) and reversible redox chemistry in the complex [Cr(tpe)2 ] 3+ containing an Earth‐abundant first row transition metal ion is enabled by ligand bite angle, inversion symmetry and ligand non‐innocence (tpe=1, 1, 1‐tris (pyrid‐2‐yl)ethane). [Cr(tpe)2 ] 3+ is competent in light‐induced energy and electron transfer processes similar to classical noble metal ion complexes.